Model Prediksi Tindakan Pencegahan Rabies untuk Menegakkan Sistem Kewaspadaan Dini (SKD) pada SMA di Kota Kendari Tahun 2025 - Annisya Syarifuddin; La Ode Muhamad Sety; Mubarak Mubarak (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Rabies is a deadly disease transmitted through animal bites, especially dogs, and is still a serious threat in Indonesia. As of April 2023, more than 31,000 bite cases have been recorded, with Southeast Sulawesi being the region with the highest cases. In Kendari City, data shows that bite cases have fluctuated since 2018. Research objectives: To develop a prediction model for rabies prevention measures to enforce an EWS in high school students in Kendari City. Research methods: Cross-sectional quantitative research, involving 350 students from three sub-districts (Baruga, Poasia, and Kadia) with independent variables in the form of knowledge, attitudes, and beliefs, and the dependent variable in the form of rabies prevention measures. Data were collected in February 2025 through a hybrid/online questionnaire. Research results: Knowledge, attitudes, and beliefs have a significant effect on rabies prevention measures in high school students in Kendari City. Knowledge is the most dominant factor (p = 0.000; Odds Ratio (B) = 8.747), followed by attitude (Odds Ratio (B) = 5.725) and belief (Odds Ratio (B) = 2.545). Students with good knowledge are 8.7 times more likely to take rabies prevention. If the three variables are at a low level, the probability of rabies prevention actions among students is 14.4%, but it increases significantly to 95.6% when all three variables are at a good level. Research Conclusion: There is a significant influence of knowledge, attitude, and belief on rabies prevention behavior to support the EWS among high school students in Kendari City in 2025. The probability of engaging in preventive behavior is 14.4% when all three variables are at a low level, but it increases significantly to 95.6% when all variables are at a high level. Knowledge contributes the most, while attitude and belief synergistically strengthen the overall effect.